Ione Getscher letter to Thomas H. Kent regarding bird sightings, April, 9, 1980 - Getscher, Ioneet al (1980)
Field notes contributed by Ione Getscher in a letter to Thomas H. Kent, May 19, 1980. The field notes contain additional species information. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed